Assimilation of protocatechuic acid and p-hydroxybenzoic acid as an aid to laboratory identification of Candida parapsilosis and other medically important yeasts. - Cooper, B H (1979)
Test for the ability of yeasts isolated from clinical specimens to utilize protocatechuic acid and p-hydroxybenzoic acid were carried out by using techniques that are commonly employed to test assimilation of carbon sources. A total of 60 isolates of Candida parapsilosis and 5 isolates of Candida humicola readily assimilated these two phenolic acids, whereas other Candida species gave uniformly negative results. Cryptococcus albidus, Cryptococcus terreus, and some isolates of Cryptococcus laurentii also assimilated protocatechuate and p-hydroxybenzoate, whereas Cryptococcus neoformans did not. Results of these tests suggest that assimilation of protocatechuate and p-hydroxybenzoate may be a useful characteristic, when used in conjunction with traditional tests, for identifying C. parapsilosis and C. albidus.